Effects of Selenium Supplementation on the Ion Homeostasis in the Reproductive Organs and Eggs of Laying Hens Fed With the Diet Contaminated With Cadmium, Lead, Mercury, and Chromium - Wu, Caimei; Li, L.; Jiang, Y. X.; Kim, Woo Kyun; Wu, B.; Liu, G. M.; Wang, Jianping; Lin, Y.; Zhang, K. Y.; Song, J. P.; Zhang, R. N.; Wu, F. L.; et al. (Frontiers in Veterinary Science, 2022)
The objective of this trial was to explore the combined toxic effects of dietary heavy metals on their depositions and ion homeostasis in reproductive organs and eggs of laying hens, as well as the alleviating action of selenized yeast. A total of 160 Lohmann pink-shell laying hens (63-week-old) were randomly divided into 4 treatments with 10 replicates of 4 hens each. The treatments were the corn-soybean meal basal diet (control; CON); the CON diet supplemented with 0.4 mg selenium /kg from selenized yeast (Se); the combined heavy metals group: the basal diet added 5 mg Cd /kg + 50mg Pb /kg +3mg Hg /kg + 5 mg Cr /kg (HEM), and the HEM diet supplemented with 0.4 mg selenium/kg from selenized yeast (HEM+Se). The dietary HEM significantly increased Cd, Pb and Hg deposition in the egg yolk and ovary, Cd deposition in the oviduct, as well as Cd and Hg deposition in the follicular wall (P < 0.05). The HEM elevated Fe concentration in the egg yolk, egg white, ovary, and oviduct (P < 0.05). The HEM decreased Mn concentration in the egg yolk, Fe, Mn, and Zn concentrations in the egg white, Cu concentration in the ovary, Mg concentration in the oviduct, as well as Ca, Cu, Zn, and Mg concentrations in the follicular walls (P < 0.05). Se addition elevated Se concentration in the egg yolk, oviduct, and follicular walls and Mg concentration (P < 0.05) in the oviduct, whereas it reduced Fe concentration in the oviduct. Both positive and negative correlations among these elements were observed. Canonical Correlation Analysis showed that the concentrations of Pb and Hg in the egg yolk were positively correlated with those in the ovary. The concentration of Cd in the egg white was positively correlated with that in the oviduct. In summary, dietary Cd, Pb, Hg, and Cr caused ion loss and depositions of HEM in reproductive organs of laying hens. Se addition at 0.4 mg/kg from selenized yeast partially attenuated toxicity of HEM on the disorders of ions.